1995
DOI: 10.1051/lait:19954-534
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacteria used as probiotics - A review

Abstract: Summary -The investigation of probiotics has been very intensive during the last decades, concentrating mainly on lactic acid and bifidobacteria. But there is also clear evidence that propionibacteria have probiotic effects. The probiotic influence is based on the production of propionic acid, bacteriocins, vitamin B 12 , better exploitation of fodder, growth stimulation of other beneficial bacteria and the ability to stay alive during gastric digestion. In Finland, large test series with piglets receiving Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 3 publications
(1 reference statement)
0
27
0
1
Order By: Relevance
“…In this sense, it has been reported that dairy propionibacteria administered alone or combined with other microorganisms increase the weight gain, feed efficiency and health of different animals such as laying hens and broilers [147], pigs [148] and calves [149,150].…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it has been reported that dairy propionibacteria administered alone or combined with other microorganisms increase the weight gain, feed efficiency and health of different animals such as laying hens and broilers [147], pigs [148] and calves [149,150].…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
“…Mantere-Alhonen [148] was the first to achieve growth promotion in piglets fed with different species of propionibacteria being P freudenreichii ssp shermanii the most effective probiotic among the species tested. When propionibacteria were fed to piglets in a daily concentration of 2 x 10 9 cfu/g, the weight gain was 9.2-14.5% higher, the fodder demand was 7.2-46.1% lower than the control group and the animals had less diarrhoea.…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
“…Propionibacteria display several promising characteristics, including the production of vitamin B12, which led to consideration of their use as human probiotics [18]. Pérez Chaia et al showed that they positively modulate intestinal microflora in mice by modifying the number of anaerobes and coliforms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential use of PAB as probiotics has been little investigated [14]. Probiotics have been defined as microbial cell preparations or components of microbial cells that have a beneficial effect on the health and well-being of the host [22].…”
Section: Introductionmentioning
confidence: 99%
“…PAB are members of the normal intestinal microflora, though not as a major component, where they are thought to play a role in the digestion of protein [12], and contribute to the production of vitamin K [6]. Some health effects of PAB have been reported; stimulation of the immune system [8,11], stimulation of the growth of bifidobacteria [3,10] and reduction of mutagen-producing faecal enzyme activity [14,21]. The ability of PAB to suppress the growth of yeasts and fungi could also have considerable therapeutic use [23].…”
Section: Introductionmentioning
confidence: 99%